An analysis of risk factors for carbapenem-resistant Enterobacteriaceae infection. (September 2022) - Gao, Yan; Chen, Meilian; Cai, Meng; Liu, Kun; Wang, Yimin; Zhou, Chunlian; Chang, Zhigang; Zou, Qi; Xiao, Shirou; Cao, Yang; Wang, Weihua; Liu, Zhuang; et al.
Highlights: CRE colonisation converse to infection rate was 36.09%. On average, it took about one week to convert from colonisation to infection. Kidney diseases, agranulocytosis, invasive procedures and CRE detection time were the risk factors for CRE infection. CRE screening should be provided to high-risk patients as early as possible, and effective intervention measures should be taken in time to avoid developing CRE infection and causing adverse consequences. ABSTRACT: Objectives: This study aims to explore the high-risk factors of carbapenem-resistant Enterobacteriaceae (CRE) infection of hospitalised patients in high-risk departments. Methods: This study is a multicentre, retrospective study. CRE screening positive patients from 1 January 2016 to 31 December 2018 of high-risk departments in five tertiary first-class teaching hospitals in Beijing collect the patients' CRE test specimen information, CRE infection information and outcomes. The patients were divided into a colonisation group and an infection group for comparative analysis. A logistic regression model was established to explore the risk factors of CRE infection. Subgroup analysis was conducted according to invasive procedures and the type of the infection. Results: In total, 344 patients were included in this study, including 85 (24.71%) colonisation and 259 (75.29%) infection; 36.09% CRE colonisation converted to infection, and the mean conversion time from colonisation to infection was 6.5 (4.0, 18.8) days. Renal disease, granulocytosis, invasive procedures and the time from hospital stay to positive CRE were the risk factors for CRE infection. The subgroup analysis showed that the rate of CRE infection in the invasive group was higher than in the non-invasive group ( P < 0.001), and the rate of exacerbation or death in the invasive group was also higher than in the non-invasive group ( P  = 0.019). The average length of ICU and hospitalisation in the healthcare-associated infection group were significantly higher than those in the community infection group, but there was no difference in the proportion of final exacerbation or death between them ( P  = 0.727). Conclusion: Kidney disease, granulocytosis, invasive procedures and CRE detection time are the risk factors for CRE infection. Carrying out CRE screening in patients as early as possible and taking effective intervention measures in time to avoid adverse consequences is all important.